(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2014)
This paper is intended to work on the social, political and culturalissues in the Fiction of Rohinton Mistry. India is a multi-lingual, multi-cultural and multi-ethnic country, andit is one of the main strains of post colonialist that transcription workshould be carried on for the sake of literary development, nationalincorporation and international co-operation.